Bismuth-based liquid alloy catalyst as well as preparation method and application thereof

By using bismuth-based liquid alloy catalysts that combine bismuth with other metals, the existing catalyst activity is solved and the preparation process is complex, achieving efficient ammonia synthesis under mild conditions and simplifying the preparation process.

CN119746880APending Publication Date: 2025-04-04HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510077861.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing liquid alloy catalysts have low activity in catalytic synthesis of ammonia and are complex in preparation, requiring special equipment and high temperature and high pressure conditions.

Method used

Bismuth is used as the substrate of the liquid alloy, combined with other metals such as Cr, Mn, Fe, Co, Ni, Cu, Mo, In, Sn, to form a strong and weak double-active center, metal oxides are prepared by precipitation method, and bismuth-based liquid alloy catalyst is obtained by calcining with bismuth ball mill.

Benefits of technology

Under mild conditions, the catalytic synthesis activity of ammonia is significantly improved, the stability is good, the preparation cost and operation difficulty is reduced, and special equipment and high-temperature and high-pressure conditions are not required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746880A_ABST
    Figure CN119746880A_ABST
Patent Text Reader

Abstract

The invention relates to a bismuth-based liquid alloy catalyst and a preparation method and application thereof, and the preparation method of the bismuth-based liquid alloy catalyst comprises the following steps: mixing a metal M source with deionized water, adding a precipitator to adjust the pH value, aging at room temperature to form a precipitate, and calcining the precipitate after post-treatment to obtain a metal oxide MOx; and carrying out ball milling on metal bismuth and the metal oxide MOx, and calcining to obtain the bismuth-based liquid alloy catalyst. The bismuth-based liquid alloy catalyst can be prepared by ball-milling and calcining a metal oxide prepared by a precipitation method and metal bismuth, the raw materials are low in cost, the method is simple, the repeatability is high, and the bismuth-based liquid alloy catalyst can be prepared in a large scale, and the prepared bismuth-based liquid alloy catalyst takes bismuth as a substrate of a liquid alloy and is combined with other metals to form strong and weak double active centers; the method can effectively reduce the limitation of a linear restriction relationship on a single metal catalytic center in the ammonia synthesis process, and can effectively realize the catalytic synthesis of ammonia under mild conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal catalysis technology, and in particular to a bismuth-based liquid alloy catalyst and a preparation method and application thereof. Background Art

[0002] From the trend of human energy utilization, it can be found that the proportion of H is gradually increasing. In the process of utilizing C-containing energy, people have gradually discovered that fossil energy is not inexhaustible, and the emission of a large amount of CO2 during the use process leads to serious environmental pollution such as the "greenhouse effect". Therefore, it can be inferred that the final and best energy source must be H2. In the actual use of H2, people found that there is an urgent problem to be solved, that is, the storage and transportation of H2. Ammonia not only has a low saturated vapor pressure of only about 10 atmospheres at room temperature (300K, 27℃), but also has a hydrogen content of up to 18% (mass fraction), so ammonia is easier to liquefy, store and transport than hydrogen. Therefore, ammonia has the potential to become an important substance for energy storage and application, and play an important role in the future global sustainable energy layout. Ammonia also has broad application prospects in traditional chemical industry and energy carriers.

[0003] Traditionally, the Haber process is used in industry to synthesize ammonia on a large scale. However, due to the high temperature and high pressure conditions required by the Haber process, the overall energy consumption of the ammonia synthesis industry is huge, and it also brings serious environmental problems. At present, conventional solid catalysts often have the problem of easy poisoning and deactivation. The liquid alloys recently studied by scientists have great advantages and can avoid the problem of poor catalyst stability. Liquid alloys have been applied to many fields such as catalysis, energy storage, and special equipment. For example, the patent with publication number CN112266002A discloses a method for catalytic synthesis of ammonia under normal pressure, in which hydrogen and nitrogen are synthesized in a reactor with liquid alloy as a catalyst under normal pressure. However, the activity of the liquid alloy catalyst in thermal catalytic synthesis of ammonia is still extremely low, and even in a small-scale selection scenario, its output is far lower than industrial demand. In addition, the method provided by the patent requires synthesis with the help of molten salt under inert gas conditions, which has high requirements for equipment and methods. In addition to this patent, the preparation process of some of the main liquid alloy catalysts is also relatively complicated, and usually requires special equipment and technology. For example, the preparation of amorphous alloy catalysts requires a liquid quenching method, which increases the preparation cost and operation difficulty. Summary of the invention

[0004] Based on this, the purpose of the present invention is to provide a bismuth-based liquid alloy catalyst and a preparation method and application thereof. The bismuth-based liquid alloy catalyst prepared by the present invention uses bismuth as the base of the liquid alloy and combines with other metals to form a strong and weak dual active center, which can effectively reduce the linear constraint relationship limitation on the single metal catalytic center in the process of synthesizing ammonia, and can effectively realize the catalytic synthesis of ammonia under mild conditions.

[0005] To achieve the above object, the present invention adopts the following technical solutions: The present invention first provides a method for preparing a bismuth-based liquid alloy catalyst, which comprises the following steps: S1. After mixing the metal M source with deionized water, adding a precipitant to adjust the pH, aging at room temperature to form a precipitate, and calcining the precipitate after post-treatment to obtain a metal oxide MO. x ; S2. Bismuth metal and the metal oxide MO x After ball milling together and calcination, a bismuth-based liquid alloy catalyst is obtained.

[0006] As a further improvement of the above solution of the present invention, in step S1, the metal M source is a salt of metal M, and the metal M is at least one of Cr, Mn, Fe, Co, Ni, Cu, Mo, In, and Sn; And / or, in step S1, the mixing is ultrasonic mixing, and the ultrasonic time is 10-60 min.

[0007] As a further improvement of the above scheme of the present invention, in step S1, the precipitant is one of NH3·H2O, KOH, NaOH, (NH4)2CO3, and Na2CO3.

[0008] As a further improvement of the above scheme of the present invention, in step S1, the pH adjustment is to adjust the pH of the solution to 9-10; And / or, in step S1, the room temperature aging time is 1 to 48 hours.

[0009] As a further improvement of the above scheme of the present invention, in step S1, the post-treatment is to wash the precipitate with deionized water and ethanol alternately by centrifugation until it becomes neutral, and then vacuum dry it at 60-90° C. for 4-12 hours; And / or, in step S1, the calcination is carried out in a muffle furnace at a temperature of 400-800° C. for 2-10 hours, and the heating rate of the muffle furnace is 2-10° C. / min.

[0010] As a further improvement of the above scheme of the present invention, in step S2, the rotation speed of the ball mill is 200-600 rpm, and the ball milling time is 1-12 h; And / or, in step S2, the calcination is carried out in a muffle furnace at a temperature of 200-500° C. in a mixture of hydrogen and argon for 2-10 hours, the heating rate of the muffle furnace is 1-5° C. / min, and the volume percentage of hydrogen in the mixture is 10%.

[0011] As a further improvement of the above solution of the present invention, in step S2, the mass percentage of the M element in the bismuth-based liquid alloy catalyst is 1% to 10%.

[0012] The present invention also provides a bismuth-based liquid alloy catalyst, which is prepared by the above-mentioned preparation method.

[0013] The present invention also provides an application of the bismuth-based liquid alloy catalyst as described above in thermal catalytic synthesis of ammonia, which comprises the following steps: loading the bismuth-based liquid alloy catalyst into one end of a U-shaped reaction tube with a sieve plate of a fixed reaction bed for synthesizing ammonia, introducing a mixed gas of N2 and H2, and heating for catalytic reaction.

[0014] As a further improvement of the above scheme of the present invention, in the mixed gas, the molar ratio of N2 and H2 is 1:1~5, and the flow rate of the mixed gas is 20~300mL / min; the temperature of the heating catalytic reaction is 200~500℃, and the pressure is 1~5MPa.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the preparation of the bismuth-based liquid alloy catalyst, the present invention first obtains the metal oxide by a precipitation method. The metal oxide can be prepared by the precipitation method. The type and ratio of the metal salt in the reaction system can be precisely controlled to flexibly adjust the composition and ratio of the final product, and the morphology and particle size of the metal particles finally obtained can be effectively regulated. The precipitation method has relatively simple equipment and operation, and the cost of the required raw materials is also low, which has significant cost advantages. The precipitation method can be prepared immediately according to the experimental purpose and in the required ratio. At the same time, the metal oxide obtained by the precipitation method can also reduce the cost. Then, the metal oxide is ball-milled with the metal bismuth and calcined to obtain the bismuth-based liquid alloy catalyst. The use of the metal oxide does not need to consider the oxidation effect of the metal M, and can also avoid the problems of the difficulty of mixing the metal M and the phase structure of the metal bismuth. In addition, due to the influence of the precipitation reaction conditions and environment, the surface of the metal oxide particles has a higher active site density and a stronger chemical adsorption capacity. In the subsequent reducing atmosphere calcination process, although the metal oxide will be reduced to metal, the active sites and chemical adsorption capacity on the particle surface will not completely disappear, but will be retained and continued to a certain extent. The invention does not require special equipment and technology, does not need to be operated in an inert atmosphere, has low-cost raw materials, a simple method, high repeatability, and can be prepared in large quantities.

[0016] 2. The bismuth-based liquid alloy catalyst prepared by the present invention has a strong interaction between the 6p orbital of Bi and the 2p orbital of N, which is conducive to the adsorption and activation of nitrogen on the active site of Bi. Bismuth is used as the substrate of the liquid alloy and combined with other metals to form a strong and weak dual active center. It exhibits good catalytic synthesis of ammonia activity under low temperature and low pressure reaction conditions and has good stability. It can effectively reduce the linear constraint relationship limitation on the single metal catalytic center in the process of synthesizing ammonia, and can effectively realize the catalytic synthesis of ammonia under mild conditions.

[0017] 3. The bismuth-based liquid alloy catalyst prepared in the present invention appears to be solid at room temperature. Due to its low melting point, it will be transformed into a liquid state for reaction during the synthesis of ammonia. The bismuth-based liquid alloy has fluidity during the reaction and will continuously refresh its interior and interface during the reaction. This alternation causes the active components to continuously roll and change at the interface, effectively preventing the active components from being poisoned by hydrogen and covering the active sites to make the catalyst inactive. The bismuth-based liquid alloy catalyst prepared in the present invention is used as a low-temperature and low-pressure ammonia synthesis catalyst, and has good catalytic effect and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The XRD pattern of Bi-Co3O4-MoO3 prepared in Example 1 of the present invention; Figure 2 The SEM and Mapping images of BiCoMo prepared in Example 1 of the present invention; Figure 3 This is the ammonia synthesis activity diagram of Test Example 1 of the present invention; Figure 4 This is the ammonia synthesis activity diagram of Test Example 2 of the present invention. DETAILED DESCRIPTION

[0019] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0021] Example 1 This embodiment provides a bismuth-based liquid alloy catalyst, and the preparation method thereof comprises the following steps: S1. Mix 5.82g of Co(NO3)2·6H2O and 3.53g of (NH4)6Mo7O 24·4H2O was dissolved in 30mL of deionized water, and ultrasonic treatment was performed for 30min to make the solid dissolve evenly. The pH was adjusted to 9 with 1mol / L NaOH solution. After aging at room temperature for 24h, the precipitate was taken out and washed alternately with deionized water and ethanol until the pH was 7. It was placed in a vacuum drying oven and dried at 80℃ for 10h. It was then placed in a muffle furnace and heated to 600℃ at a heating rate of 5℃ / min, and kept at 600℃ for 4h to obtain Co3O4-MoO3.

[0022] S2. Weigh 10g of metallic bismuth powder and 1.41g of Co3O4-MoO3 obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 400rpm, and ball mill for 10h. After the ball milling is completed, Bi-Co3O4-MoO3 is obtained; the obtained Bi-Co3O4-MoO3 is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), and the temperature is increased to 400°C at a heating rate of 2°C / min, and kept at 400°C for 4h to obtain a BiCoMo liquid alloy catalyst.

[0023] Figure 1 The X-ray diffraction spectrum of Bi-Co3O4-MoO3 prepared in this example was obtained by XRD characterization (XRD, Cu-Kα, λ=1.5406Å). Figure 1 It can be seen that the Bi-Co3O4-MoO3 prepared in this example has good crystallinity, which corresponds to the standard cards Bi (PDF#85-1331), Co3O4 (PDF#43-1003) and MoO3 (PDF#09-0209), respectively, proving that Bi-Co3O4-MoO3 is successfully prepared.

[0024] Figure 2 The BiCoMo liquid alloy catalyst prepared in this example was characterized by scanning electron microscopy to obtain a scanning electron microscope photograph. Figure 2 It can be seen that the BiCoMo liquid alloy catalyst prepared in this example is in block form at room temperature, and the distribution of Bi, Co and Mo elements is very uniform.

[0025] Example 2 S1. Dissolve 5.82g of Co(NO3)2·6H2O in 30mL of deionized water, ultrasonically treat for 30min to make the solid dissolve evenly, adjust the pH to 9 with 1mol / L NaOH solution, age at room temperature for 24h, take out the precipitate, wash it alternately with deionized water and ethanol to pH=7, place it in a vacuum drying oven, and dry it at 80℃ for 10h. Then place it in a muffle furnace, heat it to 600℃ at a heating rate of 5℃ / min, and keep it at 600℃ for 4h to obtain Co3O4.

[0026] S2. Weigh 10 g of metallic bismuth powder and 1.36 g of Co3O4 obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 400 rpm, and ball mill for 10 hours. After the ball milling is completed, Bi-Co3O4 is obtained; the obtained Bi-Co3O4 is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), and the temperature is increased to 400°C at a heating rate of 2°C / min, and kept at 400°C for 4 hours to obtain a BiCo liquid alloy catalyst.

[0027] Example 3 S1. 3.53 g of (NH4)6Mo7O 24 ·4H2O was dissolved in 30mL of deionized water, and ultrasonic treatment was performed for 30min to make the solid dissolve evenly. The pH was adjusted to 9 with 1mol / L NaOH solution. After aging at room temperature for 24h, the precipitate was taken out and washed alternately with deionized water and ethanol until the pH was 7. It was placed in a vacuum drying oven and dried at 80℃ for 10h. It was then placed in a muffle furnace and heated to 600℃ at a heating rate of 5℃ / min, and kept at 600℃ for 4h to obtain MoO3.

[0028] S2. Weigh 10g of metallic bismuth powder and 1.41g of MoO3 obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 400rpm, and ball mill for 10h. After the ball milling is completed, Bi-MoO3 is obtained; the obtained Bi-MoO3 is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), and the temperature is increased to 400°C at a heating rate of 2°C / min, and kept at 400°C for 4h to obtain a BiMo liquid alloy catalyst.

[0029] Example 4 This embodiment provides a bismuth-based liquid alloy catalyst, and the preparation method thereof comprises the following steps: S1. 8.08g of Fe(NO3)3·9H2O and 5.82g of Ni(NO3)2·6H2O were dissolved in 30mL of deionized water, and the solid was dissolved evenly by ultrasonic treatment for 30min. The pH was adjusted to 9 with 1mol / L NH3·H2O solution. After aging at room temperature for 36h, the precipitate was taken out and washed alternately with deionized water and ethanol to pH=7, placed in a vacuum drying oven, and dried at 60℃ for 24h. Then, it was placed in a muffle furnace, heated to 600℃ at a heating rate of 2℃ / min, and kept at 600℃ for 6h to obtain Fe3O4-NiO.

[0030] S2. Weigh 10 g of metallic bismuth powder and 0.699 g of Fe3O4-NiO obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 500 rpm, and ball mill for 8 hours. After the ball milling is completed, Bi-Fe3O4-NiO is obtained; the obtained Bi-Fe3O4-NiO is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), the temperature is increased to 500°C at a heating rate of 3°C / min, and the temperature is kept at 500°C for 2 hours to obtain a BiFeNi liquid alloy catalyst.

[0031] Example 5 This embodiment provides a bismuth-based liquid alloy catalyst, and the preparation method thereof comprises the following steps: S1. Dissolve 8.08g of Fe(NO3)3·9H2O in 30mL of deionized water, ultrasonically treat for 30min to make the solid dissolve evenly, adjust the pH to 9 with 1mol / L NH3·H2O solution, age at room temperature for 36h, take out the precipitate, wash it alternately with deionized water and ethanol to pH=7, place it in a vacuum drying oven, and dry it at 60℃ for 24h. Then place it in a muffle furnace, heat it to 600℃ at a heating rate of 2℃ / min, and keep it at 600℃ for 6h to obtain Fe3O4.

[0032] S2. Weigh 10 g of metallic bismuth powder and 0.55 g of Fe3O4 obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 500 rpm, and ball mill for 8 hours. After the ball milling is completed, Bi-Fe3O4 is obtained; the obtained Bi-Fe3O4 is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), the temperature is increased to 500°C at a heating rate of 3°C / min, and the temperature is kept at 500°C for 2 hours to obtain a BiFe liquid alloy catalyst.

[0033] Example 6 This embodiment provides a bismuth-based liquid alloy catalyst, and the preparation method thereof comprises the following steps: S1. Dissolve 5.82g of Ni(NO3)2·6H2O in 30mL of deionized water, ultrasonically treat for 30min to make the solid dissolve evenly, adjust the pH to 9 with 1mol / L NH3·H2O solution, age at room temperature for 36h, take out the precipitate, wash it alternately with deionized water and ethanol to pH=7, place it in a vacuum drying oven, and dry it at 60℃ for 24h. Then place it in a muffle furnace, heat it to 600℃ at a heating rate of 2℃ / min, and keep it at 600℃ for 6h to obtain NiO.

[0034] S2. Weigh 10 g of metallic bismuth powder and 0.636 g of NiO obtained in step S1, place them in the ball mill of a planetary ball mill for ball milling, set the ball milling speed to 500 rpm, and ball mill for 8 hours. After the ball milling is completed, Bi-NiO is obtained; the obtained Bi-NiO is placed in a tubular furnace for calcination, the calcination atmosphere is a mixture of hydrogen and argon (the volume percentage of hydrogen is 10%), the temperature is increased to 500°C at a heating rate of 3°C / min, and the temperature is kept at 500°C for 2 hours to obtain a BiNi liquid alloy catalyst.

[0035] Test Example 1 This test example tests the catalytic activity of the liquid alloy catalyst and the metal bismuth powder prepared in Examples 1-3 as catalysts for thermal catalytic synthesis of ammonia. The method for thermal catalytic synthesis of ammonia is as follows: 500 mg of the catalyst is loaded into one end of the U-shaped reaction tube with a sieve plate of a fixed bed reactor for synthesis of ammonia, the reaction temperature is fixed at 400°C, the reaction pressure is 4 MPa, the molar ratio of N2:H2 is 1:3, the flow rate of the mixed gas is 90 mL / min, the generated ammonia is collected and the ammonia yield is calculated. The results are as follows: Figure 3 shown.

[0036] The ammonia yield is calculated as follows: the collected ammonia is passed into a H2SO4 solution (0.1 mol / L), and NH3 is converted into NH4 in the acid solution. + , using UV spectrophotometer to calculate NH4 in H2SO4 solution + The specific method is salicylic acid-hypochlorite spectrophotometry. The specific principle is that in the presence of alkaline medium (pH = 11.7) and sodium nitrosoferricyanide, ammonia and ammonium ions in water react with salicylate and hypochlorite ions to generate a blue compound with a maximum absorption peak at 697 nm. The absorbance is measured by a spectrophotometer to quantitatively analyze the concentration of ammonia. NH4Cl is used as NH4 + The standard substance is used to prepare NH4Cl solutions of different concentrations. According to the above salicylic acid-hypochlorite spectrophotometry, a NH4 + Concentration-absorbance standard curve; the H2SO4 solution after absorbing ammonia is tested with the same test method as the standard curve and substituted into the standard curve to obtain the NH4 in the H2SO4 solution. + Concentration. Then calculate the ammonia yield according to the following formula:

[0037] Where: Represents NH4 during reaction time + The concentration difference, represents the mass of the catalyst, t Represents reaction time.

[0038] from Figure 3The results show that the BiCoMo liquid alloy catalyst prepared in Example 1 has a good ammonia synthesis reaction rate. Under the reaction conditions of 400°C, 4MPa and a mixed gas flow rate of 90mL / min, the ammonia synthesis reaction rate reaches 20.5mmol. NH3 g cat -1 h -1 In addition, it can be seen that doping Co and Mo metals in Bi has a more obvious activity improvement, and BiCoMo ternary liquid alloy has a better catalytic effect than single metal (Co or Mo) doped Bi.

[0039] Test Example 2 This test example tests the catalytic activity of the liquid alloy catalyst and the metal bismuth powder prepared in Examples 4-6 as catalysts for thermal catalytic synthesis of ammonia. The method for thermal catalytic synthesis of ammonia is as follows: 500 mg of the catalyst is loaded into one end of the U-shaped reaction tube with a sieve plate of a fixed bed reactor for synthesis of ammonia, the reaction temperature is fixed at 500°C, the reaction pressure is 2 MPa, the molar ratio of N2:H2 is 1:3, the flow rate of the mixed gas is 120 mL / min, the generated ammonia is collected and the ammonia yield is calculated (the ammonia yield calculation method is the same as that of Test Example 1). The results are as follows: Figure 4 shown.

[0040] from Figure 4 The results show that the BiFeNi liquid alloy catalyst prepared in Example 4 has a good ammonia synthesis reaction rate. Under the reaction conditions of 500°C, 2MPa, and a mixed gas flow rate of 90mL / min, the ammonia synthesis reaction rate reaches 18.9mmol. NH3 g cat -1 h -1 In addition, it is easy to find that doping Fe and Ni metals in Bi has a more obvious activity improvement, and BiFeNi ternary liquid alloy has a better catalytic effect than single metal (Fe or Ni) doped Bi.

[0041] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0042] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a bismuth-based liquid alloy catalyst, characterized in that: It includes the following steps: S1. After mixing the metal M source with deionized water, adding a precipitant to adjust the pH, aging at room temperature to form a precipitate, and calcining the precipitate after post-treatment to obtain a metal oxide MO. x ; S2. Bismuth metal and the metal oxide MO x After ball milling together and calcination, a bismuth-based liquid alloy catalyst is obtained.

2. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S1, the metal M source is a salt of metal M, and the metal M is at least one of Cr, Mn, Fe, Co, Ni, Cu, Mo, In, and Sn; And / or, in step S1, the mixing is ultrasonic mixing, and the ultrasonic time is 10-60 min.

3. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S1, the precipitant is one of NH3·H2O, KOH, NaOH, (NH4)2CO3, and Na2CO3.

4. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S1, the pH adjustment is to adjust the pH of the solution to 9-10; And / or, in step S1, the room temperature aging time is 1 to 48 hours.

5. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S1, the post-treatment is to wash the precipitate with deionized water and ethanol alternately by centrifugation until it becomes neutral, and then vacuum dry it at 60-90° C. for 4-12 hours; And / or, in step S1, the calcination is carried out in a muffle furnace at a temperature of 400-800° C. for 2-10 hours, and the heating rate of the muffle furnace is 2-10° C. / min.

6. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S2, the ball milling speed is 200-600 rpm, and the ball milling time is 1-12 h; And / or, in step S2, the calcination is carried out in a muffle furnace at a temperature of 200-500° C. in a mixture of hydrogen and argon for 2-10 hours, the heating rate of the muffle furnace is 1-5° C. / min, and the volume percentage of hydrogen in the mixture is 10%.

7. The method for preparing a bismuth-based liquid alloy catalyst according to claim 1, characterized in that: In step S2, the mass percentage of the M element in the bismuth-based liquid alloy catalyst is 1% to 10%.

8. A bismuth-based liquid alloy catalyst, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the bismuth-based liquid alloy catalyst as claimed in claim 8 in thermal catalytic synthesis of ammonia, characterized in that: It includes the following steps: The bismuth-based liquid alloy catalyst is loaded at one end of the U-shaped reaction tube with a sieve plate of the fixed reaction bed for synthetic ammonia, and a mixed gas of N2 and H2 is introduced to heat and perform a catalytic reaction.

10. The use according to claim 9, characterized in that: In the mixed gas, the molar ratio of N2 and H2 is 1:1~5, and the flow rate of the mixed gas is 20~300mL / min; the temperature of the heating catalytic reaction is 200~500℃, and the pressure is 1~5MPa.

Citation Information

Patent Citations

  • Method for catalytically synthesizing ammonia under normal pressure

    CN112266002A